Abuse of Dominant Market Position by Predatory Pricing; The Valio Case - Puisto, Aarne; Alavi, Hamed (Hasanuddin Law Review, 2016)
This article analyses the competition law related to abuse of a dominant market position using strategy of predatory pricing by undertakings in the European Union and, compares the same situation to the United States’ predatory pricing law. The purpose of this article is to survey predatory pricing as a phenomenon both within and outside the EU. Article is largely centered on the case of Valio, which is still awaiting final judgment from the Supreme Administrative Court of Finland. This case was chosen as it is extremely topical and has several unique features. The findings proved that undertakings who achieved their dominant position before the recession have significant advantage over smaller undertakings. However, they cannot necessarily afford to act on the same basis for long, which is why a model closer to that of the United States would be of benefit to control some behaviors of these undertakings. Bearing in mind that the Valio case is examined under EU law, it will be interesting to see if its judgement will be remembered as the ‘milk fallacy’ or if it will change the face of the case law as it currently stands.